PENGARUH PENDIDIKAN KESEHATAN DENGAN BOOKLET TERHADAP PENGETAHUAN IBU HAMIL TENTANG PROTOKOL KESEHATAN SELAMA PANDEMI DI PUSKESMAS MANDIANGIN BUKITTINGGI - Detty Afriyanti; Widya Nengsih; Selvia Yuliani Gusrizal (Universitas Fort De Kock, 2022)
Covid-19 infection in pregnant women has a greater impact than the group of women who are not pregnant. The design of this research was quasi-experimental with Post-Test Only Non Equivalent Control Group Design approach. The population in the study were 235 pregnant women. Sampling using purposive sampling technique with a sample size of 32 people who were divided into 2 groups. Data collection using a knowledge questionnaire. Data analysis included univariate analysis and bivariate analysis using independent t-test. The results showed that the average post-test knowledge in the control group was 14.37 and the post-test knowledge average in the experimental group was 19.00. There was a difference in the average knowledge of pregnant women between the control group and the experimental group with an average difference of 4.625 and p value = 0.000. It can be concluded that health education using booklets has a significant effect on knowledge of pregnant women about health protocols.